One‐year persistent symptoms and functional impairment in SARS‐CoV‐2 positive and negative individuals. (31st March 2022) - Nehme, Mayssam; Braillard, Olivia; Chappuis, François; Courvoisier, Delphine S.; Kaiser, Laurent; Soccal, Paola M.; Reny, Jean‐Luc; Assal, Frederic; Bondolfi, Guido; Tardin, Aglaé; Graf, Christophe; Zekry, Dina; et al.
Abstract: Background: Persistent symptoms of SARS‐CoV‐2 are prevalent weeks to months following the infection. To date, it is difficult to disentangle the direct from the indirect effects of SARS‐CoV‐2, including lockdown, social, and economic factors. Objective: The study aims to characterize the prevalence of symptoms, functional capacity, and quality of life at 12 months in outpatient symptomatic individuals tested positive for SARS‐CoV‐2 compared to individuals tested negative. Methods: From 23 April to 27 July 2021, outpatient symptomatic individuals tested for SARS‐CoV‐2 at the Geneva University Hospitals were followed up 12 months after their test date. Results: At 12 months, out of the 1447 participants (mean age 45.2 years, 61.2% women), 33.4% reported residual mild to moderate symptoms following SARS‐CoV‐2 infection compared to 6.5% in the control group. Symptoms included fatigue (16% vs. 3.1%), dyspnea (8.9% vs. 1.1%), headache (9.8% vs. 1.7%), insomnia (8.9% vs. 2.7%), and difficulty concentrating (7.4% vs. 2.5%). When compared to the control group, 30.5% of SARS‐CoV‐2 positive individuals reported functional impairment at 12 months versus 6.6%. SARS‐CoV‐2 infection was associated with the persistence of symptoms (adjusted odds ratio [aOR] 4.1; 2.60–6.83) and functional impairment (aOR 3.54; 2.16–5.80) overall, and in subgroups of women, men, individuals younger than 40 years, those between 40–59 years, and in individuals with no past medical or psychiatric history. Conclusion: SARS‐CoV‐2 infection leads to persistent symptoms over several months, including in young healthy individuals, in addition to the pandemic effects, and potentially more than other common respiratory infections. Symptoms impact functional capacity up to 12 months post infection. Abstract :